Aberrant STAT3 activation and overproduction of IL-21 in systemic lupus erythematosus: role of miR-155 and miR-21 in target genes SOCS1, PTEN and PIAS3 - Espinoza-García, Noemí; Palafox-Sánchez, Claudia Azucena; De Arellano, Adrián Ramírez; Salazar-Camarena, Diana Celeste; Rocío Félix-Murray, Katya; Marín-Rosales, Miguel; Ortiz-Lazareno, Pablo C.; Vega-Cornejo, Gabriel; Armendariz-Borunda, Juan; Muñoz-Valle, José Francisco (Frontiers in Immunology, 2026)
IntroductionSLE is a chronic autoimmune disease characterized by immune system dysregulation, including aberrant activation of B and T lymphocytes and overproduction of proinflammatory cytokines such as IL-21. Through the STAT3 signaling pathway, this cytokine plays a key role in SLE-promoting autoantibody production and immune imbalance. It has been reported that miRNAs, such as miR-155 and miR-21, could be overexpressed in SLE and contribute to the STAT3 pathway dysregulation. We aimed to analyze the association between miR-155 and miR-21 and the expression of SOCS1, PTEN, PIAS3, and IL21 in PBMC from SLE patients.Materials and methodsPBMC isolation was performed by density gradient centrifugation using Histopaque-1077, culture overnight, and seeded at a concentration of 1x106 cells/mL in 24-well flat-bottom cell culture plates for subsequent stimulation with 0.5 μg/mL ionomycin and 2.5 μg/mL PMA. The expression levels of miR-155, miR-21, SOCS1, PTEN, PIAS3, and IL21 were measured using the RT-qPCR technique. Western blotting determined the expression of SOCS1, PTEN, PIAS3, IL-21, and p-STAT3 proteins. IL-17A levels in cell culture supernatant were determined using ELISA to assess cell stimulation.ResultsOur results showed an increased expression of miR-155 and miR-21 in SLE patients compared to HC in both, stimulated and non-stimulated PBMC. The increased miR-155 and miR-21 expression were associated with a decreased gene expression of SOCS1 and PTEN. The IL21 expression was observed in stimulated PBMC with higher levels in SLE patients. These also showed lower expression of SOCS1, PTEN, and PIAS3, while levels of IL-21 were increased in total protein from PBMC, culture cell supernatants and plasma levels. Overall, p-STAT3 was increased in the PBMC of SLE patients. Finally, miR-21 inversely correlated with PIAS3 and PTEN and miR-155 with SOCS1.DiscussionThese findings highlight the association between miR-155 and miR-21 with target genes SOCS1, PTEN, and PIAS3, that may contribute to the aberrant activation of the STAT3 pathway and the overproduction of IL-21 in SLE patients.